Uneven distribution of resources in the youth linguascapes of Mongolia - Dovchin, Sender (Walter de Gruyter, 2017)
© 2017 Walter de Gruyter GmbH, Berlin/Boston. Drawing on offline and online casual interactions in the context of youth in Mongolia, on the Asian periphery, this article looks at youth mixed language practices from the perspective of "linguascapes" in order to capture the current flows of transnational linguistic resources in relation to other social landscapes. The study seeks to contribute to current discussions of the sociolinguistics of globalization by investigating to what extent and in what way resources make up linguascapes among youth groups with different access to resources. The main implication of this study is that youth linguascapes in Mongolia are fundamentally diverse, as a result of the combination of varied transcultural resources. At the same time, these resources are unevenly distributed and unequally localized.